Perfil Científico Dos Neurocirurgiões No Brasil - Ueoka, Denis Isao [UNIFESP] (2018)
Introduction: The Brazilian scientific production has grown in the last decades, but there is no study of the profile of neurosurgeon researchers in Brazil. Objectives: To describe the scientific profile of neurosurgeons in Brazil. Methods: The curriculum of neurosurgeons of the Brazilian Neurosurgery Society were analyzed in the Lattes Platform. The variables studied were: graduation from medical school and medical residency; academic training (masters, doctorate, postdoctoral and free teaching); institutional bond; national and international scientific production; Coordination of Research Project and Research Group; Orientation of Scientific Initiation, Masters and Doctorate; H Index, classification by category and geographical distribution of the researcher. Results: 1206 (52.2%) out of the 2307 neurosurgeons had curriculum Lattes. In relation to the time of graduation and medical residency, there is a slight predominance in the range of 11 to 20 years (31.75%) and < 11years (33.91%), respectively. The researchers degree profile: 15% Master's degree, 17.91% PhD, 2.73% Postdoctoral degree, 6.38% Free Teaching. 35.4% of the researchers had an institutional bond. Regarding Academic Activity: 6.46% orientation of Scientific Initiation; 6.55% Masters and 4.22% PhD. There is a scientific production of National Article (7572) and International (6028) since 1970 with 14.59% participation of researchers as Member of Editorial Board. There are 5 researchers in the Project Coordination, 48 participating in a group of research and 10 classified within categories 1 and 2. H index was identified on 400 researchers, and 355 had h<11.Conclusion: a survey of the scientific profile of neurosurgeons in Brazil was done.